Episodic future thinking: mechanisms and functions. (October 2017) - Schacter, Daniel L; Benoit, Roland G; Szpunar, Karl K
Highlights: Research on episodic future thinking has increased dramatically during the past decade. Cognitive studies have begun to separate the contributions of episodic retrieval from non-episodic processes. Studies of patient populations have shown episodic future thinking deficits in various conditions. Neuroimaging studies are identifying the role of individual regions in a core brain network that supports episodic future thinking. Episodic future thinking serves diverse functions, ranging from decision making to spatial navigation. Abstract : Episodic future thinking refers to the capacity to imagine or simulate experiences that might occur in one's personal future. Cognitive, neuropsychological, and neuroimaging research concerning episodic future thinking has accelerated during recent years. This article discusses research that has delineated cognitive and neural mechanisms that support episodic future thinking as well as the functions that episodic future thinking serves. Studies focused on mechanisms have identified a core brain network that underlies episodic future thinking and have begun to tease apart the relative contributions of particular regions in this network, and the specific cognitive processes that they support. Studies concerned with functions have identified several domains in which episodic future thinking produces performance benefits, including decision making, emotion regulation, prospective memory, and spatial navigation.